Bag cell extract inhibits tail-siphon withdrawal reflex, suppresses long-term but not short-term sensitization, and attenuates sensory-to- motor neuron synapses in Aplysia - Goldsmith, JR (J Neurosci, 1993)
The peptides released from the bag cells (bag cell peptides, BCPs) in Aplysia californica are responsible for eliciting or modulating a repertoire of behaviors preceding and accompanying egg laying. Our interest was in determining to what extent behaviors that can occur simultaneously with egg laying are modulated. To address this issue, we examined the effects of an extract (bag cell extract, BCE) that contained BCPs, as well as egg-laying hormone (ELH), an identified BCP, on both the tail-siphon withdrawal reflex and the ability of that reflex to exhibit sensitization, a simple form of nonassociative learning. In addition, we examined the ability of BCE, as well as the individual BCPs, to modulate a component of the circuitry of the reflex. Behavioral experiments indicated that BCE inhibited the baseline withdrawal reflex and suppressed long-term sensitization of the reflex while leaving short-term sensitization unaffected. These effects were not observed in animals receiving an extract of a control ganglion or in animals receiving ELH, and therefore may be attributed to the actions of one or more BCPs, but presumably not to ELH alone. Electrophysiological experiments revealed that BCE also attenuated the monosynaptic EPSP elicited in tail motor neurons by tail sensory neurons. In subsequent experiments in which the BCPs were individually applied, only one BCP, beta-BCP, significantly attenuated the EPSPs. This effect was independent of narrowing of the presynaptic action potential. Taken together, these results suggest a novel behavioral modification attributed to BCPs, inhibition of the tail-siphon withdrawal reflex, and suggest a possible locus of action and peptide candidate for this effect. In addition, these experiments raise the possibility that BCPs may exert a long-lasting effect (> 24 hr), selectively blocking a simple form of long-term memory.